FOTO IKLAN LAYANAN MASYARAKAT TENTANG KESEHATAN DALAM KARYA FOTOGRAFI KREATIF - Adia Damar Syamsuri; Ida Susanti (Jurnal Ilmiah Publipreneur, 2013)
This research aims at creating public service advertisement photos about public health in a creative photographic work. Â The public health themes used are six aspects e.i. smoking, obesity, narcotics, liquor, epilepsy, HIV and AIDS. The contents are about convincing people to live healthier and leave the negative things that are detrimental to health. In addition, the researcher wants to remove negative paradigm that is always present in the minds of the public about the disease called a nerve disorder, epilepsy or â€œAyanâ€. Making of photos are done with tools and materials in accordance with the concept of assisted photo shoots with the help of Digital Imaging. The researcher uses the technique of shooting High Key. He uses a mini studio with two lights flash strobe for shooting the object man and light tent mini studio for shooting objects in the form of inanimate objects with small to moderate size.